The effect of the Pancasila student profile strengthening project on bullying behavior of students (MA Nurul Iman Bandung City) - Rahman, Fadliany Aulia; Nurtantri, Syara; Nurhasanah, Siti; Roji, Agus Fahrul; Hidayat, Rijky Akhmad; Ulfah, Ulfah (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This research is driven by the rising prevalence of bullying behaviour among students, encompassing verbal, physical, mental, and sexual forms, which constitutes a significant issue within the educational system. This study aims to evaluate the impact of the project focused on enhancing the Pancasila student profile theme of awakening the soul and body as a solution to address student bullying behaviour. This study employs a quantitative methodology utilising a descriptive analytical technique. The data gathering method was a survey strategy utilising a questionnaire instrument given randomly to tenth-grade pupils. Data analysis was conducted via simple linear regression and product moment correlation, facilitated by SPSS version 25 software. The findings indicated a substantial impact of the Pancasila student profile enhancement initiative, centred on the topic of awakening the soul and body, on the bullying behaviour of tenth-grade students, with a significance value of 0.000 (0.000 < 0.05). The project's impact on enhancing the profile of Pancasila students regarding the theme of developing their character and physical well-being in relation to student bullying behaviour is 62.6%. The study's results indicate that the project aimed at enhancing the Pancasila-themed student profile significantly impacts the bullying behaviour of tenth-grade students.